Zatoichi's Revenge Based on a Short Story by Kan Shimozawa - Inoue, Akira; Morita, Fujio; Katsu, Shintaro; Miki, Norihei; Tsubouchi, Mikiko (Zatoichi: The Blind Swordsman Collection, 2019)
Nearing the village of his sensei, Zatoichi decides to pay the teacher a visit, only to learn that he has been murdered and his daughter forced into prostitution. Ichi's investigation into these injustices uncovers a corrupt alliance between government officials and criminals, putting the blind swordsman on a bloody path of retribution in one of the series' darkest entries. [www.criterion.com]